Bacteriological Profile and antibiotic susceptibility pattern of tracheal secretions isolates among intensive care unit patients at tertiary care hospital - Bhavin K Prajapati; Priyanka Harshadbhai Gohel; Atit D Shah; Hiral J Shah; Kaival K Kothari; Jayshri D Pethani (Wolters Kluwer Medknow Publications, 2022)
Introduction: Respiratory infections are associated with high morbidity and mortality, especially in critically ill patients. The excessive use of broad-spectrum antibiotics has led to the development of drug resistance, thus resulting in the emergence of pathogens which are difficult to treat. Materials and Methods: A total of 632 tracheal secretions were received in the Bacteriology section of the microbiology department of a tertiary care hospital from November 2019 to February 2020. Tracheal secretions were processed for culture according to standard operating procedures. Identification, phenotype detection, and antibiotic sensitivity testing were performed by automated VITEK-2 Compact system. Results: In total, 632 tracheal secretions were received during the study period, 559 cultures yielded significant pathogens and no organisms were isolated in 73 cultures. Among the Gram-negative organism 540 (97%), Klebsiella pneumoniae (30%) was the most common isolates. Gram-positive organisms 12 (2%) and Candida spp. 7 (1%) were isolated. The most common phenotype detected in Escherichia coli and K. pneumoniae was extended-spectrum beta-lactamase producer. Conclusions: K. pneumoniae was the most common isolate from tracheal secretion among intensive care unit patients. Colistin, followed by tigecycline, was found to be the most susceptible antibiotics. K. pneumoniae was found to be sensitive to tigecycline (69%) with minimum inhibitory concentrations of ≤ 1. 0.6%. K. pneumoniae was colistin resistant.